A 22 year assessment of deforestation and restoration in riparian forests in the eastern Brazilian Amazon. (4th November 2014) - NUNES, SÂMIA S.; BARLOW, JOS; GARDNER, TOBY A.; SIQUEIRA, JOÃO V.; SALES, MÁRCIO R.; SOUZA, CARLOS M.
SUMMARY: Brazilian environmental law imposes more restrictions on land-use change by private landowners in riparian forests than in non-riparian forest areas, reflecting recognition of their importance for the conservation of biodiversity and key ecosystem services. A 22-year time series of classified Landsat images was used to evaluate deforestation and forest regeneration in riparian permanent preservation areas over the past two decades, focusing on the municipality of Paragominas in the state of Pará in eastern Amazonia. There was no evidence that riparian forests had been more effectively protected than non-riparian forests. Instead, deforestation was found to be comparatively higher inside riparian permanent preservation areas as recently as 2010, indicating a widespread failure of private property owners to comply with environmental legislation. There was no evidence for higher levels of regeneration in riparian zones, although property owners are obliged by law to restore such areas. A number of factors limit improvements in the protection and restoration of riparian forests. These include limited awareness of environmental compliance requirements, the need for improved technical capacity in mapping the distribution and extent of riparian forests and the boundaries of private properties, and improved access to the financial resources and technical capacity needed to support restoration projects.